Pemilihan Transportasi Bus Antar Kota Antar Provinsi (AKAP) Dengan Metode Simple Additive Weighting (SAW), Weighted Product (WP), dan Promethee Berbasis Android - Riyadi, Achmad; Andryana, Septi; Winarsih, Winarsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
The migrants who have increased every year made bus transportation be one of the most widely used transportation for the Wonogiri’s people to go home to their hometowns. In Wonogiri district, bus transportation is available from various companies, ranging from local companies and non local who have primacy facilities, services, and a diverse bus fleet. The application of a decision support system is to make it easier for prospective passengers to make choices according to the desired criteria can be done using the Simple Additive Weighting, Weighted Product, and Promethee methods. The methods calculates the value of each criteria, weight criteria, criteria type, and is easy to apply to solve problems related to multi-criteria. There are 5 criteria used and 17 different bus companies as alternatives. The existence of this system is expected to make it easier for prospective passengers to decide the bus according to the desired criteria.
Keywords: Promethee; Simple Additive Weighting; Weighted Product